PEMANFAATAN VIDEO UNTUK MENINGKATKAN AKTIFITAS DAN HASIL BELAJAR MATERI DAKWAH RASULULLAH SISWA SMK - Fithriyanti, Fithriyanti (Jurnal Kajian Pembelajaran dan Keilmuan, 2020)
Abstract This research aims to increase the activity and learning outcomes of students on material proselytizing of the prophet in the class XF SMK SMTI Pontianak. This research consist of 2 (two) cycles with each meeting takes time 3x45 minutes. Each cycle consisted of planning, implementation, observation, and analysis section.To know classmanagement, teacher and student;s observation sheet was used. The results showed that using of video that can improve the activity and student learning outcomes on material proselytizing of the prophet in class XF SMK SMTI Pontianak. It can be seen from the increase in average grade from 70 to 72.82 and the percentage of students who pass the tes rosefrom 56.52% in the first cycle becomes 82.61% in the second cycle. Keyword: Video, Learning Outcomes, Da’wah Rasulullah SAW